Environmental Physics Study of Natural Renewable Energy Resources in Socotra, Yemen - Saif Serag; Echchelh Adil (Indonesian Journal of Social and Environmental Issues (IJSEI), 2021)
The best sources for energy production are renewable energy sources such as wind, solar, tidal energy, and other energy sources, which ensure the sustainability of power generation for life and even avoid the problems producing from fossil fuels combustion, which leads to air pollution, climate change, and many problems, but the main problem that facing Especially in developing countries, such as Yemen is the lack of a database and sufficient information to know the available capabilities for electricity production by natural resources that region possesses, especially the remote islands from the main power plant, which are powered by diesel and gas generators. In this paper, we will provide and list all-natural resources that possessed Socotra island, and its analysis to provide a clear vision that enables exploitation of these resources in the future on a clear scientific basis, as the study shows that mean wind speed is approximately 9.8 m/s, solar radiation reaches 180 kWh/m2, all these values ​​confirm island has the total ability to generate electricity from these sources with high efficiency.